Moderation Study of Student Organization (Muslim and Non-Muslim Student Activity Units) Diversity: Student Ethics and Habits - Baidhowi; Moch. Yusuf Efendi (Studies in Learning and Teaching, 2024)
Moderation is a concept that means a middle way that promotes balance in the form of beliefs and morals expressed in the religious attitudes of individuals or groups amidst diversity. The aim of this research is to investigate student organization moderation at The State University of Semarang, specifically focusing on Muslim and non-Muslim student activity units on ethics and habituation. This study uses a quantitative method by collecting data through a questionnaire. Selection of the sample using an accidental sampling technique. The number of research respondents was 120 students of Semarang State University—data analysis using SPSS. The main point on comprehending and applying religious teachings in a way that ensures their consistency, moderation is known as religious moderation. Here, moderate refers to not being excessive or extreme. Thus, it is the practice of religion that is moderated here rather than the religion itself. Since religion derives from the All-Perfect God, it is flawless in and of itself. Everyone interprets and applies religious teachings differently, though.